2014
DOI: 10.1063/1.4867246
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of relative permittivity of LTCC ceramic at different temperatures

Abstract: Devices based on LTCC (low-temperature co-fired ceramic) technology are more widely applied in high temperature environments, and the temperature-dependent properties of the LTCC material play an important role in measurements of the characteristics of these devices at high temperature. In this paper, the temperature-dependence of the relative permittivity of DuPont 951 LTCC ceramic is studied from room temperature to 500 °C. An expression for relative permittivity is obtained, which relates the relative permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Because the working temperature of an RF cable is also typically limited up to 125 °C, 11,33,34,36) limitation in temperature is a common problem even in the conventional resonance methods. Though the use of antennas is one of the solutions for the limitation, 37) design of the thermal-static antennas should be a difficult process because the impedance of the antennas can be changed by changing temperature. The measurement accuracy was not as good as that of conventional resonance methods.…”
Section: Benefits and Limitations Of The Measurement Techniquementioning
confidence: 99%
“…Because the working temperature of an RF cable is also typically limited up to 125 °C, 11,33,34,36) limitation in temperature is a common problem even in the conventional resonance methods. Though the use of antennas is one of the solutions for the limitation, 37) design of the thermal-static antennas should be a difficult process because the impedance of the antennas can be changed by changing temperature. The measurement accuracy was not as good as that of conventional resonance methods.…”
Section: Benefits and Limitations Of The Measurement Techniquementioning
confidence: 99%
“…Through Equations (2) and (3), it can be concluded that the resonant frequency of the sensor is affected by the relative permittivity of the dielectric material. The dielectric constant of the alumina ceramic material increases with the increasing temperature [ 25 , 26 ], causing the resonant frequency of the temperature sensor to decrease.…”
Section: Working Principle Of the Temperature Sensormentioning
confidence: 99%
“…In this respect, the resonator method with planar circuits, such as stripline and ring resonators, can be used for investigating inhomogeneity because they can provide the dielectric property of a circuit substrate around the resonator fabricated on the substrate. [22][23][24][25] The length of a λ=2 resonator at 100 GHz is 1.5 mm; thus, the stripline resonator method can realize local dielectric measurement at a resolution of several millimeters. Furthermore, the dielectric permittivity of a transmission line whose length is precisely known can be approximately estimated based on the phase of the transmission coefficient in a simple manner.…”
Section: Introductionmentioning
confidence: 99%